Identification of potential inhibitors of the main protease from feline infectious peritonitis virus using molecular docking and dynamic simulation approaches - Khan, Mohd Yasir; Shah, Abid Ullah; Duraisamy, Nithyadevi; Moawad, Nadine; ElAlaoui, Reda Nacif; Cherkaoui, Mohammed; Hemida, Maged Gomaa (PeerJ, 2025)
Background Feline infectious peritonitis virus (FIPV) is one of cats’ most serious viral infections. The FIPV infection induces a complicated syndrome in the affected cats, including immunosuppression and severe inflammatory conditions. Unfortunately, vaccines are unable to provide complete prevention in cats from getting infected with these viral infections. There is ongoing research on preparing antiviral therapies against FIPV in cats. However, these are still in clinical trials and have not been fully approved by the drug authorities in many countries, including the USA. Targeting the main viral proteases is one of the promising trends in the drug design of many viral diseases, including coronaviruses. The main goal of the current study was to repurpose and test the efficacy of some known antiviral drugs to treat FIPV infection in cats by targeting the FIPV main protease (Mpro). Methods We used the in-silico prediction and molecular docking tools to screen and identify some drugs targeting FIPV-MPro to achieve these goals. The research method was started by building a screening pharmacokinetic associated variables of the compound, then used to design a new potential inhibitor by employing the docking and molecular dynamic simulation to evaluate the interaction of all complexes using the standard dynamics cascade protocol of Biovia Discovery studio. Results Our results show that out of the 15 antiviral and immunomodulatory compounds, the top-ranked inhibitors for the FIPV-Mpro are reference standard inhibitor (N3), Sofosbuvir, and the GS-441524, out of which GS-441524 was suggested as Mpro-inhibitor on the basis of further investigation through molecular dynamics simulation method. In conclusion, our results confirmed the potential applications of the predicted FIPV-Mpro inhibitors either independently or in combination with other immune-modulatory compounds. Further in vitro and in vivo studies are encouraged to test the efficacy of these identified compounds as potent inhibitors for the Mpro of the FIPV in cats. This study will pave the way for the development of novel drugs that treat FIPV infection in cats.
Keywords: FIPV; Mpro; In silico design; Molecular docking; Antiviral; Dynamic simulation; Nucleoside analogs; GS441524; Sofosbuvir; FCoV